Litigating Fair Use - Cendali, Dale M. (The Columbia Journal of Law & the Arts, 2025)
This Article’s topic is “Litigating Fair Use.” What follows is a discussion of techniques a litigator can use to win a case and in so doing, help shape the development of fair use law. Fair use is well-recognized as one of the “most troublesome” doctrines in all of copyright. There are many famous cases where the district court wrote a compelling opinion holding that something was or was not fair use, and then was reversed by a court of appeals in an equally certain-sounding and compelling opinion holding the opposite. Sometimes we have seen the Supreme Court take yet another view, or multiple views, where there is a dissent and perhaps a concurrence as well. Court after court has noted that fair use requires “case-by-case analysis” that carefully balances the four statutory fair use factors—plus sometimes other considerations as well—rather than rigid application of “bright-line rules.” The overall intent is to help judges reach a result that furthers the bedrock constitutional principle that copyright laws “promote the progress of science and useful arts.” The flexible nature of fair use provides an opportunity—and perhaps a challenge—for a copyright litigator to not only figure out how best to apply existing precedent to create a persuasive argument, but also how to invite the creation of new precedent. Copyright law, and fair use specifically, starts from Congress’s statutory text, is informed by the Copyright Office’s guidance, is interpreted by the courts, and is analyzed by law professors. But litigators are not passive in this process; rather, they play an important role as well. In fact, the modern litigator often is in a uniquely good position to affect the development of fair use. These days, litigators practice all around the country, with admissions in many courts and pro hac vice appearances before others. This cross-country practice creates the opportunity—and in fact the necessity—to keep abreast of trends and splits across the various circuits, to figure out what best to argue in a given case, and thereby to hope to advance the law and their clients’ interests. Simply put, if the law of fair use is developed by case precedent, then the people whose arguments impact cases—that is, litigators—can help shape the law. How do litigators do it? In this Article, I will discuss three of the primary tools in the litigator’s proverbial tool kit: law, facts, and persuasion. At the end of the day, these three things determine every fair use outcome. The art of litigating fair use is found in the gaps between precedent, when a litigator’s cutting-edge case is one about which reasonable minds may disagree. It is in those gaps where the litigator shines, because the law there is at its most malleable and the ability to persuade is most important. And with fair use, there are a lot of those gaps.